Sprayed ZnO thin films for ethanol sensors - Sahay P.P.; Tewari S.; Jha S.; Shamsuddin M. (My University, 2025)
The electrical characteristics of ZnO thin films prepared by spray pyrolysis, have been studied for ethanol sensors. The sensitivities of the films are measured at various temperatures and concentrations of ethanol. It is observed that the sensitivity increases with increasing working temperature. At higher ethanol concentrations, the sensitivity increases more rapidly with increasing temperature. Further, the films show fast response and recovery times at higher working temperatures. The sensing mechanism of the films towards ethanol vapour has been explained. © 2005 Springer Science + Business Media, Inc.